The Preparation of Liposomes derived from Mixed Micelles of Lecithin added by Sodium Cholate, followed by Dialysing using Hemoflow High Flux F60S - Erni Hernawati Purwaningsih; Rolf Schubert (Makara Journal of Health Research, 2010)
Liposomes are used for drug carriers meaning that drugs are incorporated in the membrane or the vesicle of the liposomes. In this study, liposomes were prepared from mixed micelles, consisting of phosphatidylcholine, without or with cholesterol and sodium cholate was added in several ratios namely 0.44; 0.55; 0.63; 0.70; 0.90 and 1.10. After the preparation, the sodium cholate has been removed by a dialysis membrane, using the Hemoflow High Flux, which is generally used for haemodialysis. The Hemoflow High Flux is a tool in an effort to obtain a simple, quick, effective method for removing sodium cholate in the process of preparing liposomes. The effectiveness of this tool was proved by the particle size of the liposome which was measured by the Malvern Particle Sizer. The particle size of the liposome consisting of phosphatidylcholine (PC) without cholesterol and with cholesterol was 63-68 nm at all ratios and approximately 125 nm at the ratio of 0.55; 0.63; 0.70, respectively. The particle size of the liposome tended to be smaller after dialyzing, although the concentration of lipids tended to increase. However, a large amount of buffer solution has to be used with this method.